Sociodemographic characteristics and vaping motives as potential correlates of early vaping initiation - Aisha Al-Naimi; Fatma Al-Obaidli; Reem Al-Rashdi; Fatima Al Zahraa Chokor; Mohammed Al-Hamdani (Frontiers in Public Health)
BackgroundVaping’s popularity has particularly increased among young people, with its prevalence varying across different regions, including the Middle East. The health impacts of vaping, especially when initiated early, are a growing concern.AimsThis study aimed to investigate the correlates of early vaping initiation (EVI) and explored the sociodemographic characteristics and vaping motives influencing EVI among vapers from Arab countries.MethodsAn online cross-sectional survey recruited 428regular vapers, aged 18–60 who resided in Arab countries at the time of the study. Sociodemographic and vaping motives data were collected. Stepwise logistic regression was used to examine the factors associated with EVI.ResultsThe study findings revealed that older participants and expats have lower odds of EVI. Males and vapers from Qatar had around 4–5 times the odds of EVI as compared to females and those from Egypt, respectively.ConclusionTargeted social marketing and education campaigns may benefit groups at risk of EVI, including residents of Qatar, males, and those who are strongly influenced by social media or who have friends or family members who vape. Reducing EVI is particularly important, as vaping often begins at an early age, and early intervention is vital to prevent early initiation and subsequent addiction.